2014
DOI: 10.1055/s-0034-1371299
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in cognitive flexibility: Influence of gray-matter volume, functional connectivity and trait impulsivity

Abstract: Cognitive flexibility, a core aspect of executive functioning, is required for the speeded shifting between different tasks and sets. Using an interindividual differences approach, we examined whether cognitive flexibility, as assessed by the Delis-Kaplan card-sorting test, is associated with gray matter volume (GMV) and functional connectivity (FC) of regions of a core network of multiple cognitive demands as well as with different facets of trait impulsivity. The core multipledemand network was derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 56 publications
(81 reference statements)
3
13
0
Order By: Relevance
“…Furthermore, in bvFTD patients, the number of categories found in the WCST has previously been associated with atrophy in the superior temporal gyrus (Lagarde, et al, 2013). Regarding the impact of insular atrophy on executive functioning, and supporting our findings, previous studies on healthy individuals (Muller, Langner, Cieslik, Rottschy, & Eickhoff, 2015;Ruscheweyh, et al, 2013) reported a strong association between GM in the insula and several EF (i.e., cognitive flexibility, working memory and inhibitory control). Lesion studies have implicated the insula in response inhibition (Swick, Ashley, & Turken, 2008) and verbal fluency (Baldo, Schwartz, Wilkins, & Dronkers, 2006).…”
Section: The Relationship Between Gm Atrophy and Impairments In Execusupporting
confidence: 89%
“…Furthermore, in bvFTD patients, the number of categories found in the WCST has previously been associated with atrophy in the superior temporal gyrus (Lagarde, et al, 2013). Regarding the impact of insular atrophy on executive functioning, and supporting our findings, previous studies on healthy individuals (Muller, Langner, Cieslik, Rottschy, & Eickhoff, 2015;Ruscheweyh, et al, 2013) reported a strong association between GM in the insula and several EF (i.e., cognitive flexibility, working memory and inhibitory control). Lesion studies have implicated the insula in response inhibition (Swick, Ashley, & Turken, 2008) and verbal fluency (Baldo, Schwartz, Wilkins, & Dronkers, 2006).…”
Section: The Relationship Between Gm Atrophy and Impairments In Execusupporting
confidence: 89%
“…Other tasks of cognitive flexibility have also been shown to be influenced by trait impulsivity levels (e.g. Müller et al ., ). Therefore, all participants completed the Barratt Impulsiveness scale (BIS‐11; Patton et al ., ) and their total score was used as a trait measure of impulsivity.…”
Section: Methodsmentioning
confidence: 97%
“…Four large‐scale networks, implicated in motor control, working memory, cognitive flexibility, and affective processing, which have repeatedly been shown to be affected in HD, were chosen for assessing patterns of covariance in GM volumes. For this purpose, ROIs were selected separately for each of the predefined cortico‐striatal networks, based on previously published meta‐analyses [Amft et al, ; Hardwick et al, ; Müller et al, ; Rottschy et al, ] and extracted using a 6‐mm radius sphere and the coordinates of each ROI as a centre. Coordinate‐based ALE meta‐analyses [Eickhoff et al, ; Turkeltaub et al, ] allow for specifying voxels that are less sensitive to noise and are based on activations derived from a multitude of different, domain‐specific neuroimaging studies.…”
Section: Methodsmentioning
confidence: 99%